Kualitas Pelayanan Program Jaminan Kesehatan Nasional pada Pusat Kesehatan Masyarakat di Cengkareng Jakarta Barat - Firda Febriyanti; Nida Handayani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The National Health Insurance Program (Jaminan Kesehatan Nasional or JKN) is a government initiative aimed at ensuring equitable, accessible, and affordable healthcare services for all Indonesian citizens. Since its implementation in 2014, the program has covered more than 90% of the population; however, several challenges remain, particularly concerning the quality of services at primary healthcare facilities such as community health centers (puskesmas). This study aims to analyze the quality of JKN services at the Cengkareng Public Health Center, West Jakarta, using the five dimensions of service quality proposed by Parasuraman: tangibles, reliability, responsiveness, assurance, and empathy. The research employed a descriptive qualitative method through in-depth interviews, direct observations, and document analysis involving healthcare workers and JKN patients. The findings indicate that the overall service quality at Puskesmas Cengkareng remains suboptimal. The tangibles and assurance dimensions are relatively good, while reliability, responsiveness, and empathy are still lacking. Major complaints include long waiting times, poor doctor–patient communication, and unfriendly staff attitudes. These findings highlight the need for improving human resource professionalism, strengthening service management systems, and conducting periodic evaluations to enhance the overall quality and patient satisfaction among JKN participants.